2005
DOI: 10.1089/hum.2005.16.271
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Inflammatory Hyperalgesia by Herpes Vector-Mediated Knockdown of Nav1.7 Sodium Channels in Primary Afferents

Abstract: Induction of peripheral inflammation increases the expression of the Nav1.7 sodium channel in sensory neurons, potentially increasing their excitability. Peripheral inflammation also produces hyperalgesia in humans and an increase in nociceptive responsiveness in animals. To test the relationship between these two phenomena we applied a recombinant herpes simplex-based vector to the hindpaw skin of mice, which encoded both green fluorescent protein (GFP) as well as an antisense sequence to the Nav1.7 gene. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 22 publications
2
84
0
Order By: Relevance
“…In rodent models vector delivery from the skin has been achieved by application to depilated skin [7,56] or by subcutaneous injection into the footpad but the structure and innervation of human skin is quite different from that of the rodent, and vector delivery will need to be optimized if biologically meaningful effects are to be achieved. Nonetheless, the studies to date provide encouragement that gene transfer may ultimately prove to be useful in the treatment of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent models vector delivery from the skin has been achieved by application to depilated skin [7,56] or by subcutaneous injection into the footpad but the structure and innervation of human skin is quite different from that of the rodent, and vector delivery will need to be optimized if biologically meaningful effects are to be achieved. Nonetheless, the studies to date provide encouragement that gene transfer may ultimately prove to be useful in the treatment of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Among the gene products expressed in primary nociceptors, the voltage-gated sodium channel isoform Na V 1.7 and the peptide neurotransmitter calcitonin gene related peptide (CGRP) are two gene products that experimental evidence indicates may play an important role in pain perception. Yeomans, Wilson and colleagues have reported that an HSV vector coding a sequence antisense to Na V 1.7, applied to the skin prevents the increase in Nav1.7 expression caused by CFAinduced inflammation in transduced DRG neurons and that this effect correlated with a reduction in the development of hyperalgesia in both C and A-delta thermonociceptive tests [56]. More recently, the same group has shown that an HSV vector coding a sequence antisense to CGRP reduces CGRP expression in transduced DRG neurons with concomitant reduction in nociceptive neurotransmission in-vivo [57].…”
Section: Hsv Vectors To Reduce Expression Of Endogenous Genes In the mentioning
confidence: 99%
“…In rats receiving carrageenan injection into the hind paw, the peripheral inflammation was associated with the up-regulation of Na v 1.7 level and TTX-sensitive Na + current amplitude in the DRG neurons (96). In rat DRG neurons, herpes vector-mediated knockdown of Na v 1.7 prevented the development of hyperalgesia in response to Freund's adjuvant (63). These results suggested that increased expression or activity of Na v 1.7 was involved in the development of inflammatory hyperalgesia; erythermalgia is a model disease that is useful for understanding of pathology and treatment of inflammatory hyperalgesia.…”
Section: +mentioning
confidence: 99%
“…Importantly, Na v 1.7 also plays a role in eliciting intolerable pain in inflammation (62,63) and diabetic neuropathy (64,65), Na v 1.7 being the first convincing molecular target of therapeutic drugs against pain. In this context, Table 2 may be informative; it summarizes our previous studies showing that density and activity of cell surface Na v 1.7 were up-or down-regulated by various therapeutic drugs and cellular signals in cultured bovine adrenal chromaffin cells (which are embryologically derived from the neural crest and are homologous to sympathetic ganglion neurons).…”
Section: Introductionmentioning
confidence: 99%
“…The first of these involves knockdown of the Nav1.7 sodium channel. 10 The blockade of sodium channels (for example, by lidocaine) has been known for many decades to be an effective means of blocking pain. However, there are nine known varieties of voltage-gated sodium channels in the body, and several of them are found in the membranes of sensory neurons, both nociceptive and non-nociceptive (for example, touch afferents).…”
Section: Gene-silencing Vectorsmentioning
confidence: 99%